Rural Entrepreneurship for Sustainable Economic Development in Chandel District, Manipur, India ‒ An Exploration - Onahring, B. D.; Singh, Kh. Devananda (Universitas Negeri Semarang, 2020)
Entrepreneurship in the rural context has got ample opportunities for capital formation, sustainable development and economic growth. In rural India, the intervention of enterprise development institutions was less, due to lack of the awareness to the beneficiaries and the technical dearth of these institutions. The Government of India has initiated various programs through many institutions under government and non-government sectors since decades. These programs ensured sufficient training and development programs on entrepreneurship development on one hand, but, the other has to adopt the effective and efficient entrepreneurial traits for entrepreneurship development. This article is a humble effort to understand the various entrepreneurial traits through a review of literature. It also focuses to draw the various entrepreneurial traits among rural entrepreneurs in the study area. The statistical population was 215 enterprises out of which 43 enterprises were selected as the sample through stratified random sampling method. Beside descriptive statistics, the study has adopted Cronbach’s Alpha test, factor analysis and Kaiser-Meyer-Olkin (KMO) as well as Bartlett’s Test through MS-Excel and SPSS Software for analyses. The paper found that the entrepreneurs in rural Chandel district wanted to enjoy more financial freedom, supports from family members, needed for achievement. Moreover, they also showed a more inner sense of responsibilities which thereby arouse passion for business. The findings of the research activity could help the policy planners to enhance the economics of rural entrepreneurs in Chandel district of Manipur, India.